Physical, strength and acoustic properties of lightweight cement composite with preplaced chemically-treated crumb rubber - Shah S.N.; Beddu S.; Yap S.P.; Putra A.; Othman M.N.; Yuen C.W.; Mo K.H. (Elsevier Ltd, 2025)
The valorisation of waste tyre crumb rubber (CR) as a sustainable construction material can alleviate environmental pollution and save natural aggregate consumption. However, its use in cement composite can result in a significant loss of strength due to weak adhesion and the non-uniform dispersion of CR. To compensate this strength loss, this research aims to investigate the innovative incorporation of chemically treated CR via the preplaced aggregate mixing (PM) method in producing a lightweight cement composite. The CR was treated with different chemicals, namely soaking in potassium permanganate and sulphuric acid solutions. The findings reveal a significant improvement in compressive strength (up to 160%) and water absorption reduction (from 20% to 175%) using the chemically treated CR and PM mixing methods, producing a lightweight cement composite with a density of about 1535 kg/m3. The SEM observation demonstrates the improvement in the CR?paste interface due to the treatment of the CR and the PM mixing methods, and due to the chemical treatment, which improved the wettability of the CR. On the other hand, the sound absorption and noise reduction coefficient of the chemically treated CR lightweight cement composite was almost similar for both the normal mixing (NM) and the PM methods. Overall, the results demonstrate that the CR treatment with sulphuric acid is promising for the PM method to produce a lightweight cement composite. ? 2023 The Authors